0
$\begingroup$

$\lvert \frac{x^2-2x+3}{x^2-4x+3}\rvert\le1\Rightarrow x\le0$

How is the proof. If I separate the denominator with triangle inequality,

$\lvert \frac{x^2-2x+3}{x^2-4x+3}\rvert\le \frac{\lvert x^2-2x+3\rvert}{\lvert x^2-2x+3 \rvert-\lvert 2x\rvert}\rvert \ge1$

Which means that the triangle inequality should stay a strict inequality, so $x^2-2x+3$ and $2x$ have opposite signs. And the discriminant of the former is negative, therefore the roots are complex, in particular the graph doesn't touch the x-axis. One can insert any value to determine its sign, for example at $0$ gives $3$, so $x$ has to be negative.

Is there another possibility, without much text to prove it ?

$\endgroup$
  • $\begingroup$ Consider two cases: $x^2-2x+3\leq x^2-4x+3$, or $x^2-2x+3\leq -(x^2-4x+3)$. You will find that you only have the first case, that is, $x^2-2x+3\leq x^2-4x+3$, which implies that $x\leq0$. $\endgroup$ – m-agag2016 Dec 19 '16 at 11:16
2
$\begingroup$

What you want is

$$\left|\frac{x^2-2x+3}{x^2-4x+3}\right|\le1\iff-1\le\frac{x^2-2x+3}{x^2-4x+3}\le1$$

Beginning with the left inequality:

$$-1\le\frac{x^2-2x+3}{x^2-4x+3}\iff\frac{x^2-2x+3}{x^2-4x+3}+1\ge0\iff\frac{2x^2-6x+6}{x^2-4x+3}\ge0\iff$$

$$\frac{x^2-3x+3}{(x-1)(x-3)}\ge 0\iff (x-1)(x-3)>0\;\text{ (why?)}\implies x<1\;\text{or}\;x>3$$

Now you do the other inequality and take the intersection of both solution sets.

$\endgroup$
  • $\begingroup$ $(x-1)(x-3)>0$ in line 4 $\endgroup$ – Khosrotash Dec 19 '16 at 11:41
  • $\begingroup$ @Khosrotash Excellent catch! Thanks, edited. $\endgroup$ – DonAntonio Dec 19 '16 at 11:51
0
$\begingroup$

WLOG let $$\dfrac{x^2-2x+3}{x^2-4x+3}=\cos y$$ where $y$ is real

$$(1-\cos y)x^2+2x(2\cos y-1)+3(1-\cos y)=0$$

$$\implies x=\dfrac{1-2\cos y\pm\sqrt{(2\cos y-1)^2-3(1-\cos y)^2}}{(1-\cos y)}$$

$$=\dfrac{1-2\cos y\pm\sqrt{\cos^2y+2\cos y-2}}{(1-\cos y)}$$

Now the denominator is non-negative.

Hence we need $$\sqrt{\cos^2y+2\cos y-2}\le2\cos y-1$$

$$\iff\cos^2y+2\cos y-2\le(2\cos y-1)^2\iff3(\cos y-1)^2\ge0$$ which is true

$\endgroup$
  • $\begingroup$ @DonAntonio, I meant this. Thanks $\endgroup$ – lab bhattacharjee Dec 19 '16 at 12:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.